Critical materials: demand-side resource efficiency measures for sustainability and resilience - National Engineering Policy Centre’s (NEPC) Working Group on Materials and Net Zero; Jolly, Mark R. (Royal Academy of Engineering, 2024)
This report provides an overview of the underutilised policy options for achieving reductions in our demands for critical materials and therefore our dependency on imports of scarce materials. This includes both existing uses of critical materials, and future ones associated with low-carbon technologies. The UK is economically and physically dependent on many materials that are mined elsewhere, and specific technological components that are not made here. Recent supply chain crises have driven increasing concern about the growing need for ‘critical’ materials, as the projected demands for these are likely to outstrip available supplies. This poses a risk to the resilience of the UK; if material demand significantly exceeds supply, it would interfere with not only economic prosperity but also the capacity of the UK to achieve the infrastructure transformation required to reach net zero. Expansion of demand for critical materials also comes with environmental and social harm that would work against global goals of mitigating climate change and of a just transition to net zero. These impacts are often not visible to the public or decisionmakers.
© Royal Academy of Engineering
Keywords: net zero; sustainability; circular economy